ANALISIS KINERJA SUMBER DAYA MANUSIA PADA PT BANK RAKYAT INDONESIA (PERSERO), TBK. KABUPATEN PINRANG - Satar, Muhammad (Universitas Muhammadiyah Parepare, 2019)
This study aims to explain and analyze the influence of factors of education, motivation, mutation and promotion of positions in relation to the performance of human resources and what factors are the least dominant contribution to the human resources performance at PT. Bank Rakyat Indonesia (Persero), Tbk Pinrang Regency. The population in this study were employees of PT. Bank Rakyat Indonesia (Persero), Tbk Pinrang Regency, with the census method, all existing employees as well as respondents.Data collection used was observation and questionnaire. The data obtained were then analyzed using descriptive statistics and multiple linear regression. The results showed that the variables of education, motivation, mutation, and promotion simultaneously had a positive and significant effect on employee performance at PT. Bank Rakyat Indonesia (Persero), Tbk Pinrang Regency. Mutation variable is the least dominant variable on the human resources performance at PT. Bank Rakyat Indonesia (Persero), Tbk Pinrang Regency.